Identifying fungal-host associations in an amphibian host system. - Alexandra Alexiev (Public Library of Science (PLoS), 2021)
Host-associated microbes can interact with macro-organisms in a number of ways that affect host health. Few studies of host-associated microbiomes, however, focus on fungi. In addition, it is difficult to discern whether a fungal organism found in or on an ectotherm host is associating with it in a durable, symbiotic interaction versus a transient one, and to what extent the habitat and host share microbes. We seek to identify these host-microbe interactions on an amphibian, the Colorado boreal toad (Anaxyrus boreas boreas). We sequenced the ITS1 region of the fungal community on the skin of wild toads (n = 124) from four sites in the Colorado Rocky Mountains, across its physiologically dynamic developmental life stages. We also sampled the common habitats used by boreal toads: water from their natal wetland and aquatic pond sediment. We then examined diversity patterns within different life stages, between host and habitat, and identified fungal taxa that could be putatively host-associated with toads by using an indicator species analysis on toad versus environmental samples. Host and habitat were strikingly similar, with the exception of toad eggs. Post-hatching toad life stages were distinct in their various fungal diversity measures. We identified eight fungal taxa that were significantly associated with eggs, but no other fungal taxa were associated with other toad life stages compared with their environmental habitat. This suggests that although pre- and post-metamorphic toad life stages differ from each other, the habitat and host fungal communities are so similar that identifying obligate host symbionts is difficult with the techniques used here. This approach does, however, leverage sequence data from host and habitat samples to predict which microbial taxa are host-associated versus transient microbes, thereby condensing a large set of sequence data into a smaller list of potential targets for further consideration.